Multiparameter single-molecule fluorescence spectroscopy reveals heterogeneity of HIV-1 reverse transcriptase:primer/template complexes - Rothwell, P. J. (The National Academy of Sciences, 2003)
By using single-molecule multiparameter fluorescence detection, fluorescence resonance energy transfer experiments, and newly developed data analysis methods, this study demonstrates directly the existence of three structurally distinct forms of reverse transcriptase (RT):nucleic acid complexes in solution. Single-molecule multiparameter fluorescence detection also provides first information on the structure of a complex not observed by x-ray crystallography. This species did not incorporate nucleotides and is structurally distinct from the other two observed species. We determined that the nucleic acid substrate is bound at a site far removed from the nucleic acid-binding tract observed by crystallography. In contrast, the other two states are identified as being similar to the x-ray crystal structure and represent distinct enzymatically productive stages in DNA polymerization. These species differ by only a 5-Å shift in the position of the nucleic acid. Addition of nucleoside triphosphate or of inorganic pyrophosphate allowed us to assign them as the educt and product state in the polymerization reaction cycle; i.e., the educt state is a complex in which the nucleic acid is positioned to allow nucleotide incorporation. The second RT:nucleic acid complex is the product state, which is formed immediately after nucleotide incorporation, but before RT translates to the next nucleotide.